(untitled) (Pedagogical Horizons, 2019)
Teachers are a key factor for an inclusive school system in Germany, studies often focus on cooperation between teachers. However, the perspective of head teachers s often missing, even though they are the central agents of a school. The following article takes a closer look at how head teachers try to implement an inclusive education system at their school and how they try to initiate an inclusive attitude. The data presented here is from a longitudinal study with secondary School teachers and head teachers from North Rhine Westphalia.